Insect-computer hybrid robot achieves a walking gait rarely seen in nature by replacing the anisotropic natural leg spines with isotropic artificial leg spines - Cao, Feng (2021)
This paper demonstrates that our developed beetle–computer hybrid legged robot achieves backward walk, which is impossible by intact beetles themselves in nature. Judging from the curvature of the natural leg spine, we hypothesized that the natural spine has an anisotropic function: the natural spine would provide foot traction only in forward walk but not in backward. The hypothesis was verified as beetles hardly walk backward due to often slips. We then designed an artificial leg spine, which isotropically functions in walk: the foot traction was increased and slipless walk was achieved in both backward and forward walk with the artificial spines being implanted into the beetle legs. For these investigations, a wireless communication device, or “backpack,” was mounted and wired to a live beetle for electrically stimulating leg muscles to remotely modulate leg motions and to perform the forward and backward walk on demand. Overall, the beetle hybrid robot revealed the anisotropic function of the natural leg spine and also achieved the backward walk, which the intact beetle cannot intrinsically perform.